Smart English Adventure: Empowering Interactive Learning for SDN Pabaki 019 - Rosmala, Dewi; Tri Noerdin, Choerunnisa Septiani; Pasya, Trisha Azzhara; Garnadi, Danang; Rahman, Taufiqur (Institut Teknologi Nasional, Bandung, 2025)
The English learning process at SDN Pabaki 019 involving grade 1 and 2 students still faces several challenges such as limited access to interactive learning media and time-consuming manual assessments. To overcome these problems, an interactive web-based learning application called Smart English Adventure was developed and implemented in the classroom. This application includes features such as teacher-managed content delivery, gamification quizzes with automatic evaluation, and flexible access for students. The development process follows the Software Development Life Cycle (SDLC), which includes the planning, design, implementation, testing, and deployment stages. A total of 60 students and 20 teachers were involved in this initiative. Feedback was collected through structured interviews, with 85% of students showing increased enthusiasm and engagement. The findings showed that this application significantly increased motivation and supported teachers in managing and evaluating learning. This program shows potential for replication in similar educational settings.